Capacity building to boost information and communication skills inside an institute of research (Journal of EAHIL, 2023)
To enhance its visibility, the Library of the Istituto Superiore di Sanità (ISS) along with the Scientific Communication Unit of the same institution delivered a set of informal online training sessions, or webinars, on their fields of expertise: information retrieval, publication, effective communication, and research evaluation, specifically addressed to internal users. The collaboration was extremely useful in terms of improved knowledge on skills available among the personnel of these two services. It increased trust in the competencies of internal staff and at the same time it contributed to develop awareness of the value of the services rendered. Skills to use available online resources for training were improved as well as ISS staff cohesion favouring the development of new collaborations.